Protocol for the collection of leaf area index (LAI) for yield estimation - Mathieu, Renaud; Quicho, Emma; Satapathy, Sushree (International Rice Research Institute, 2024)
Work package 4 maps rice areas using remote sensing, geographic information system (GIS), and crop modeling. This work builds on the Remote sensing-based Information and Insurance for Crops in Emerging economies (RIICE, http://www.riice.org/) co-developed by IRRI and implemented in South and Southeast Asian countries. RIICE technology is being introduced across Africa to enhance its rice monitoring system. A set of field protocols and forms was developed for seasonal field data collection. This protocol covers guidelines for the collection of Leaf Area Index (LAI) measurement at the rice monitoring locations. LAI is an important yield-determining factor for field grown crops, specifically for rice. The document The information collected are being used to assess the accuracy of the rice and non-rice maps.